The Impact of Spiritual-Transformational Leadership in Advancing Organizational Culture at LPD Al-Bahjah - M. Syamsul Ma’arif Ma’shum; Abdus Salam; Iman Subasman; Ade Aspandi (Journal of General Education and Humanities, 2026)
This study addresses the growing challenge faced by Islamic da’wah institutions in balancing managerial effectiveness with the preservation of spiritual values. Many religious organizations struggle to integrate performance-based leadership with transcendental and prophetic principles, leading to either managerial stagnation or value dilution. In response to this issue, this research aims to examine how a spiritual-transformational leadership model is constructed at the Al-Bahjah Da'wah Development Institute (LPD) and how it shapes organizational culture and institutional commitment. This study employs a qualitative design grounded in a constructivist paradigm. Data were collected through systematic field observation, in-depth interviews with organizational actors, and analysis of institutional documentation. The data were analyzed using thematic interpretation involving coding, categorization, and reflective triangulation to ensure credibility and analytical rigor. The findings reveal that leadership at LPD Al-Bahjah is built on the integration of tawhid-based values, moral exemplarity (uswah), a visionary da’wah orientation, and the structured empowerment of human resources. This integration generates a religious-adaptive organizational culture characterized by collective worship practices, high member loyalty, ethical innovation, and sustained institutional growth. The study demonstrates that spiritual and transformational dimensions function synergistically rather than separately, forming a leadership model that strengthens organizational identity, commitment, and resilience amid contemporary social change.